Junk food consumption trends point to the need for retail policies - Jensen Madrigal, Melissa Lorena (2021)
The term “junk food” is generally understood to include processed foods and beverages that are high in calories, added sugars, sodium, and saturated fat (1). These products are harmful because excessive consumption is associated with increased risk of negative health outcomes (e.g., obesity, hypertension, and cancer) (2). In response, a range of strategies have been tried to discourage consumption of these foods, ranging from guidance in the Dietary Guidelines for Americans to limit calories from these foods, to the USDA’s “Smart Snacks” regulations that control what can be sold in schools, to industry self-regulation promises to improve the nutritional quality of products marketed to children. But have things gotten better?